Salt of life [videorecording (DVD)] = Gianni e le donne - Di Gregorio, Gianni; De Franciscis, Valeria, 1915-2014; Santagata, Alfonso, 1947- (Zeitgeist Films, 2012)
A middle-aged retiree has become invisible to all the women of Rome, regardless of age or relation. He contends with a demanding mother; a patronizing wife; a slacker daughter; and a wild party-girl neighbor who uses him, as a dog walker. Watching his codger friends snare beautiful young girlfriends on the sun-kissed cobblestones of Trastevere, Giovanni tries his polite, utterly gracious best to generate some kind of extracurricular love life, with both hilarious and poignant results.